Collaboration Between Human–Robot Interaction Based on CDPR in a Virtual Reality Game Environment - Dang Tri Dung; Nguyen Minh Trieu; Nguyen Truong Thinh (Advances in Human-Computer Interaction)
This paper describes several thrilling motion games on virtual reality (VR) platforms to evaluate human–robot interaction (HRI) with the support of cable-driven parallel robot (CDPR). In experimental studies, the user sat on a moving platform of the CDPR, which gives the user a real feeling by wearing a head-mounted display (HMD) to create a virtual surrounding environment. HRI differs significantly from human-to-human interaction due to the artificial nature of robots and the technological limitations in replicating human-like communication, adaptability, and emotional understanding. Different contexts were given to evaluate HRI when the overall interaction context is complex in the presence of a generated dynamic real-world environment for humans with real feelings. A configuration is proposed to simulate operation in CDPR-based games so that users can experience interactions under different scenarios. This study describes the system model with the connection of possible solutions, high effectiveness, and proposed concept performance. In addition, the experimental results show that the HRI system with the VR environment works well and effectively, the connection between the hardware and the software performs synchronously to create a real feeling for players in a virtual environment. After the experiments, VR has helped improve the virtual environment simulation, assisting the players to increase their get into the game, retain system knowledge, and improve player interaction. It can be concluded that when players participate in VR with the support of CDPR, it can help patients improve clinical results in rehabilitation or simulate operations in hazardous environments, especially in the Vietnam scenario.